Equine-assisted counseling and psychotherapy : healing through horses - Sheade, Hallie (New York, NY : Routledge, 2021)
"Equine-Assisted Counseling and Psychotherapy offers a comprehensive guide to the practice of working with equines in a psychotherapeutic setting. Mental health and equine professionals will come away from the book with a strong understanding of both the theoretical and practical aspects of equine-assisted counseling"--
Partnering with equines in equine-assisted counseling and psychotherapy -- Nature of equines -- Philosophical domains in relational equine-partnered counseling -- Counseling environments in equine-assisted counseling and psychotherapy -- The treatment team in equine-assisted counseling and psychotherapy -- Facilitating relational equine-partnered counseling -- Integration of counseling theory in equine-assisted counseling and psychotherapy -- Practice equine-assisted counseling and psychotherapy across the lifespan -- Counseling and psychotherapy formats in equine-assisted counseling and psychotherapy -- Implementing equine-assisted counseling and psychotherapy with different client populations -- Ethical considerations in equine-assisted counseling and psychotherapy -- Risk management considerations in equine-assisted counseling and psychotherapy -- Program design in equine-assisted counseling and psychotherapy -- Research issues in equine-assisted counseling and psychotherapy.
OCLC-licensed vendor bibliographic record.
Keywords: Horses -- Therapeutic use; Psychotherapy; Human-animal relationships -- Psychological aspects; PSYCHOLOGY / Psychotherapy / Child & Adolescent; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychotherapy / General